ANALISIS HASIL PENGECORAN PASIR RODA GIGI LURUS BERBAHAN ALUMINIUM 1100 DAN 6063 TERHADAP SIFAT MEKANIK - Ilham Azmy; Dinar Dwi Rachmadi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
Spur gear is a toothed-shaped machine component which works by friction each other to transmit high efficiency rotational movement on shafts. This requires spur gear to possess robust mechanical properties. The sand-casting technique is widely known as a simple manufacturing process to produce high quality mechanical products with less failure. Moreover, aluminium is an alloy which owns good mechanical properties, corrosion resistance and castability. Hence, the research aims to conduct manufacturing process of spur gear using sand-casting technique made from 1100 and 6063 aluminium which followed by comparing mechanical characteristics of hardness and wear resistance. The casting process initially begins by designing and fabricating patterns, then preparing the mold and silica sand along with the aluminium melting process at temperature 600oC in a furnace, which ends by pouring the molten aluminium into the sand mold. After the spur gear was obtained, mechanical testing was examined to evaluate its hardness and wear resistance values. From the results, it was clearly found that spur gear product made from aluminium 6063 possess high hardness value (58.4 HV) and the lowest wear rate reduction (0.000827 mm3/minute). Thus, spur gear made from 6063 aluminium has the best mechanical characteristics which affects long lifespan.